2007
DOI: 10.5334/ijic.202
|View full text |Cite
|
Sign up to set email alerts
|

A literature review on integrated perinatal care

Abstract: Context: The perinatal period is one during which health care services are in high demand. Like other health care sub-sectors, perinatal health care delivery has undergone significant changes in recent years, such as the integrative wave that has swept through the health care industry since the early 1990s.Purpose: The present study aims at reviewing scholarly work on integrated perinatal care to provide support for policy decisionmaking.Results: Researchers interested in integrated perinatal care have, by ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 44 publications
1
39
0
1
Order By: Relevance
“…However, levels of collaboration can vary. A review of 64 studies investigating care integration in perinatal services, focussing on the collaboration between midwives and physicians, found that less than 20% of these concerned individual clinical practice, and most focussed on the effectiveness of intervention programmes such as smoking cessation services (Rodríguez and des Rivières-Pigeon, 2007). It concluded that small groups of health professionals collaborating to deliver maternal and child health services appear appropriate for both patients and care providers.…”
Section: Introductionmentioning
confidence: 99%
“…However, levels of collaboration can vary. A review of 64 studies investigating care integration in perinatal services, focussing on the collaboration between midwives and physicians, found that less than 20% of these concerned individual clinical practice, and most focussed on the effectiveness of intervention programmes such as smoking cessation services (Rodríguez and des Rivières-Pigeon, 2007). It concluded that small groups of health professionals collaborating to deliver maternal and child health services appear appropriate for both patients and care providers.…”
Section: Introductionmentioning
confidence: 99%
“…Integration literature suggests that improved coordination of care makes a difference in terms of effective support for new mothers and families, particularly those with additional needs for psychosocial support. 8 Currently in Australia, this level of coordination is not the case. 1 The impact of the fragmentation of the health system on health service delivery and health outcomes has been well documented 9 and numerous attempts are being made at a service level to address these concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Even though much has been written about the organisation of perinatal care [24] and many researchers stress the importance of cooperation in the chain of care in supporting new parents [2527], we have only been able to find a few scientific studies on interprofessional cooperation between different facilities in the same chain of care. The mother’s emotional response and relationship to the infant were strengthened in cases where the midwives and district nurses had undergone joint breastfeeding training [28].…”
Section: Introductionmentioning
confidence: 99%